“Wildness Without Wilderness”: Review of Irus Braverman, Wild Life: The Institution of Nature - Menely, Tobias (Humanimalia, 2016)
Irus Braverman, Wild Life: The Institution of Nature. Stanford, CA: Stanford University Press, 2015. 342 pp. $24.995 pbk.